Relationship of Industry 4.0 Readiness on Individual Innovativeness of Telkom Corporate University Employee in Bandung (The Indonesian Journal of Business Administration, 2021)
Massive advancement of technology is affecting the industry in Indonesia so that many businesses force to shifting into digital technology. This shifting is known as industry 4.0. The state of the Covid-19 pandemic also has a role in accelerating the shift in business processes. This shifting process requires Indonesian human capital to have the proper knowledge, skills, attitude, and culture. Even better, if it is supported by capable big data analytical capabilities. Furthermore, Indonesian human capital must also have high innovative behavior, especially at the individual level. It will affect the company's innovation level and ultimately at the national level as a country. Indonesia is a country with potential and has a lot of resources but is still lacking in terms of digital talent and innovation at the individual level to take advantage of its advantages. Telkom CorpU is a function within Telkom Indonesia which focuses on training and human capital development. Therefore, this research was conducted on Telkom CorpU employees in Bandung as the vanguard of human capital in Telkom Indonesia. This research is a quantitative research. Data was collected by filling out a questionnaire that was distributed to all Telkom CorpU employees at random (random sampling) and obtained 77 employees who filled in as a sample. The questionnaire was compiled based on the industry readiness theory 4.0 and Individual Innovativeness which consisted of 58 question items which were then processed using SPSS 21 with the multi-linear regression method. In this study, researchers created two regression models, namely the main variable regression of knowledge, hard skills, soft skills, attitudes, big data analytics, individual values and beliefs towards individual innovation. In the second model, the researcher added demographic factors to see the effect and increase the power of the regression model. The results of the regression consistently show that there is a significant relationship between aspects of knowledge (p <0.05), hard skills (p <0.05), soft skills (p <0.1) and big data analytics (p <0.1) on the variable readiness 4.0 for innovation. individual Telkom CorpU employees. So that the regression model is a robust model.. Individual Innovativeness is a need for employees in dealing with rapidly changing business conditions. The readiness variable for industry 4.0 has a real influence on the level of innovativeness that employees have so that it must be a concern and continue to be improved by the company if you want to have digital talent that is capable of facing industry 4.0. Keywords: Human Capital Readiness, Big Data Analytic, Culture, Readiness industry 4.0, Individual innovativeness